2016
DOI: 10.5350/dajpn2016290202
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Turkish version of the Adult ADHD Self-Report Scale (ASRS-v1.1) in a sample of Inpatients with alcohol use disorder

Abstract: Psychometric properties of the Turkish version of the Adult ADHD Self-Report Scale (ASRS-v1.1) in a sample of inpatients with alcohol use disorder Objective: The Adult Attention Deficit Hyperactivity Disorder (ADHD) Self-Report Scale (ASRS) allows dimensional self-rating assessment of ADHD according to DSM-IV. The Turkish version of the scale was validated in university students. The aim of the present study was to evaluate psychometric properties of the Turkish version of the ASRS in a sample of inpatients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
17
1
2
Order By: Relevance
“… 25 , 26 The Turkish version of the scale was previously validated on a sample of university students. 27 Specifically, in a sample of patients with AUD, psychometric characteristics of the Turkish version were analyzed by Evren et al, 28 and satisfactory properties were found. In the present study, the 18-item version was used in order to evaluate the severity of IN and HI symptoms.…”
Section: Methodsmentioning
confidence: 99%
“… 25 , 26 The Turkish version of the scale was previously validated on a sample of university students. 27 Specifically, in a sample of patients with AUD, psychometric characteristics of the Turkish version were analyzed by Evren et al, 28 and satisfactory properties were found. In the present study, the 18-item version was used in order to evaluate the severity of IN and HI symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, actually we evaluated the probable ADHD rather than the diagnosis of ADHD, and it is suggested that the severity of ADHD symptoms may change according to the sample, the scale that is used to measure ADHD symptoms, and design of the study [75]. Although currently Turkish versions of structured and semi-structured clinical interviews are introduced for adults, they are not validated in populations with SUD, whereas ASRS was validated in these populations, including the Turkish version [54,55]. Third, female patients may have a different profile concerning psychopathology, BPD, NS and ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…The scale was validated in Turkish in a sample of university students previously [53]. Specifically, in a sample of patients with alcohol use disorder, psychometric characteristics of the Turkish version have been analysed [54], in which satisfactory properties have been found. In the present study, 18-item version was used in order to evaluate the severity of IN and HI symptoms.…”
Section: Adult Adhd Self-report Scale (Asrs)mentioning
confidence: 99%
“…The Turkish version of ASRS has demonstrated good reliability and validity in university students [92]. Also, in a sample of patients with AUD, psychometric characteristics of Turkish version have been analysed by Evren et al [93], in which satisfactory properties have been found. Cronbach's alpha was 0.85 for IN, 081for HI and 0.89 for ASRS in the present study.…”
Section: Methodsmentioning
confidence: 99%